Theory of constraints: review and bibliometric analysis - Ikeziri, Lucas Martins; Souza, Fernando Bernardi de; Gupta, Mahesh C.; de Camargo Fiorini, Paula (International journal of production research, 2019)
This paper presents a bibliometric analysis of the Theory of Constraints (TOC) research i.e. a total of 1009 journal articles published since 1984. From a bibliometric point of view, the state of the art was mapped and research gaps in the scientific literature identified, creating opportunities for future research. The Production area leads in number of publications, and applications in the Process of Ongoing Improvement in general have been receiving less attention from academics. It is also worth noting that the International Journal of Production Research has the highest concentration of published works on TOC. The results show that TOC is in continuous development with a trend of growth and therefore demands additional inquiry. The main contributions of this work are: (a) presenting a comprehensive historical review and bibliometric analysis on TOC in a manner not yet illustrated in the literature; (b) addressing potential implications and directions for the IJPR community on TOC research; and (c) offering avenues for future research on how to advance the extant literature of TOC.